How To Achieve Employee Performance Faster? - Astuti, Sih; Riyanto, Fery; Wulandari, Tjahjani; Ahmad, Mubashir (Jurnal Mebis, 2024)
Human resources are an essential component in an organization, where good employee performance is vital to the organisation's survival. To achieve optimal performance, companies need to meet the needs of employees, recognize them as assets, and create an environment that supports psychological well-being.This study aims to examine and analyze the effect of employee engagement on employee performance mediated by psychological well-being and job satisfaction. This study used the population of employees of Panti Wilasa Citarum Hospital, which amounted to 205 people. Sampling using non-random sampling with purposive sampling technique. Using the SPSS analysis tool IBM SPSS 23 Software version. The study's results explain that the independent variables in this study have a positive effect on employee performance mediated by psychological well-being, which means that this study proved that job satisfaction is individual. Each individual has a different level of satisfaction according to the value system that applies to him.